Design and construction of a plastic melting pot for low density polyethylene (LDPE) (1999)
In this project a melting pot was designed and constructed using available local materials. This pot was used to melt plastic resin without the resin-changing colour (turning brown). The project was divided into two parts: the design and construction aspect and the control aspect. A good temperature control was incorporated to achieve high quality output. The construction was carried out using galvanized mild steel. In this project a melting pot was designed and constructed using available local materials. This pot was used to melt plastic resin without the resin-changing colour (turning brown). The project was divided into two parts: the design and construction aspect and the control aspect. A good temperature control was incorporated to achieve high quality output. The construction was carried out using galvanized mild steel. It consists of a cylindrical enclosure that is divided into two chambers: the upper and larger one house the melting unit, the lower chamber houses sensing element of the temperature control equipment. The instrument used for the temperature control is a thermostat which has a temperature range of 0-200°. The dimension of the material used for the fabrication was based on the least thermal difference so that equilibrium can be achieved in a short time .Tests carried out after the construction of the prototype confirmed the relevancy of the project. The pot melted the plastic resin and flowed without change of colour.